PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DIVISI AKUNTANSI DI CV. ARUM SINAR SEJAHTERA DEMAK (STIE Cendekia Karya Utama, 2021)
This study aims to examine and determine the effect of work discipline, work environment on employee performance at CV. Arum Sinar Sejahtera Demak. Data collection was carried out by distributing questionnaires to employees of CV. Arum Sinar Sejahtera Demak. as many as 50 respondents. Data analysis in this study used multiple linear analysis. Based on the results of the t test in this study, it shows that work discipline does not have a significant effect on employee performance with a significance value of 0.49. The work environment has a positive and significant influence on employee performance with a significance value of 0.00. The result of determination test (R2) is 0.587, which means that the independent variable (work discipline and work environment) on the dependent variable (employee performance) is 58.7%. The results of the analysis on the F test state that the variables of work discipline and work environment together have a significant influence on employee performance at CV. Arum Sinar Sejahtera Demak with a significance level of 0.000